2017
DOI: 10.1097/mcg.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy of All-Trans Retinoic Acid With Ursodeoxycholic Acid in Patients With Primary Sclerosing Cholangitis

Abstract: GOALS To perform an exploratory pilot study of all-trans retinoic acid (ATRA) combined with ursodeoxycholic acid (UDCA) in patients with primary sclerosing cholangitis (PSC). BACKGROUND PSC is a progressive disorder for which there is no accepted therapy. Studies in human hepatocyte cultures and in animal models of cholestasis indicate that ATRA might have beneficial effects in cholestatic disorders. STUDY ATRA (45 mg/m2/day, divided and given twice daily) was combined with moderate-dose UDCA in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…All‐ trans retinoic acid (ATRA), which activates the nuclear receptor complex FXR‐Retinoid X receptor (RXR), was evaluated for PSC in a pilot study of UDCA+ATRA and was shown to significantly decrease alanine aminotransferase (ALT) and complement‐4 levels. However, reduction in ALP levels was not significant …”
Section: Farnesoid X Receptor Agonistsmentioning
confidence: 79%
“…All‐ trans retinoic acid (ATRA), which activates the nuclear receptor complex FXR‐Retinoid X receptor (RXR), was evaluated for PSC in a pilot study of UDCA+ATRA and was shown to significantly decrease alanine aminotransferase (ALT) and complement‐4 levels. However, reduction in ALP levels was not significant …”
Section: Farnesoid X Receptor Agonistsmentioning
confidence: 79%
“…Among others, alkaline phosphatase (ALP), alanine aminotransferase (ALT) and 7‐α‐hydroxy‐4‐cholesten‐3‐one (C4), a bile acid precursor, were measured at baseline, week 12 and after washout. AtRA treatment in combination with the application of UDCA led to a significant decrease in C4 and in serum ALT . There was also a trend towards a decrease of mean serum ALP, although statistical significance was not reached ( P =.09).…”
Section: Vitamin a Treatment In Psc Patientsmentioning
confidence: 86%
“…In 2011, in a collaboration of Yale University and the Mayo Clinic, vitamin A in the form of atRA was orally applied for the first time as an investigational drug in 19 PSC patients with incomplete response to UDCA. 41 All patients enrolled (n=19) received 45 mg atRA per m 2 body surface area and day over a period of 12 weeks followed by a washout period of the same duration. Due to headache (n=2), tinnitus (n=1) and biliary obstruction (n=1) 4 out of 19 patients withdrew.…”
Section: Vitamin a Treatment In Psc Patientsmentioning
confidence: 99%
“…When used alone or in combination with UDCA, atRA significantly reduced the bile acid pool size and improved liver conditions in cholestatic rodent models . A limited clinical trial of atRA in patients with PSC supports this mechanism in humans …”
Section: Introductionmentioning
confidence: 87%
“…19,20 A limited clinical trial of atRA in patients with PSC supports this mechanism in humans. 21 Cenicriviroc (CVC) is a novel antagonist for both C-C chemokine receptor 2 and 5 (CCR2 & CCR5) that are expressed in many inflammatory cells, including neutrophils, T cells and monocytes. 22,23 It has demonstrated potent anti-inflammatory effects by blocking chemokine-activated immune responses and has been shown to reduce liver fibrosis in animal models of nonalcoholic steatohepatitis (NASH) and alcoholic liver injury.…”
mentioning
confidence: 99%